DNA condensing effects and sequence selectivity of DNA binding of antitumor noncovalent polynuclear platinum complexes - Malina, Jaroslav; Farrell, Nicholas P; Brabec, Viktor (Inorganic chemistry, 2014)
The noncovalent analogues of antitumor polynuclear platinum complexes represent a structurally discrete class of platinum drugs. Their chemical and biological properties differ significantly from those of most platinum chemotherapeutics, which bind to DNA in a covalent manner by formation of Pt-DNA adducts. In spite of the fact that these noncovalent polynuclear platinum complexes contain no leaving groups, they have been shown to bind to DNA with high affinity. We report here on the DNA condensation properties of a series of noncovalent analogues of antitumor polynuclear platinum complexes described by biophysical and biochemical methods. The results demonstrate that these polynuclear platinum compounds are capable of inducing DNA condensation at more than 1 order of magnitude lower concentrations than conventional spermine. Atomic force microscopy studies of DNA condensation confined to a mica substrate have revealed that the DNA morphologies become more compact with increasing concentration of the platinum complexes. Moreover, we also found that the noncovalent polynuclear platinum complex [{Pt(NH3)3}2-μ-{trans-Pt(NH3)2(NH2(CH2)6NH2)2}](6+) (TriplatinNC-A) binds to DNA in a sequence-dependent manner, namely, to A/T-rich sequences and A-tract regions, and that noncovalent polynuclear platinum complexes protect DNA from enzymatic cleavage by DNase I. The results suggest that mechanisms of antitumor and cytotoxic activities of these complexes may be associated with their unique ability to condense DNA along with their sequence-specific DNA binding. Owing to their high cellular accumulation, it is also reasonable to suggest that their mechanism of action is based on the competition with naturally occurring DNA condensing agents, such as polyamines spermine, spermidine, and putrescine, for intracellular binding sites, resulting in the disturbance of the correct binding of regulatory proteins initiating the onset of apoptosis.
Keywords: Neoplasms; Base Sequence; sekvence nukleotidů; Organoplatinum Compounds; protinádorové látky; Humans; organoplatinové sloučeniny; nádory; Antineoplastic Agents; DNA; lidé